Circulating microRNAs and Kallikreins before and after Radical Prostatectomy: Are They Really Prostate Cancer Markers?. (9th October 2013) - Egidi, Maria Giulia; Cochetti, Giovanni; Serva, Maria Rita; Guelfi, Gabriella; Zampini, Danilo; Mechelli, Luca; Mearini, Ettore
Abstract : The aim of our study was to monitor serum levels of two miRNAs (miR-21 and miR-141) and three KLKs (hK3/PSA, hK11, and hK13) before and 1, 5, and 30 days after radical prostatectomy, in order to characterize their fluctuations after surgery. 38 patients with prostate cancer were included. miR-21 and miR-141 were quantified through real-time PCR, while ELISA assays were used to quantify hK3 (PSA), hK11, and hK13. Both miR-21 and miR-141 showed a significant increase at the 5th postoperative day, after which a gradual return to the preoperative levels was recorded. These findings suggest that miR-21 and miR-141 could be involved in postsurgical inflammatory processes and that radical prostatectomy does not seem to alter their circulating levels. Postoperative serum kallikreins showed a significant decrease, highlighting the potential usefulness of kallikreins apart from PSA as potential prostate cancer markers.